Trees of Eastern North America - Nelson, Gil, 1949-; Spellenberg, Richard; Earle, Christopher J. (Book collections on Project MUSE., 2014)
Covers 825 species, including all the native and naturalized trees of the United States and Canada as far west as the Great Plains. Descriptions present details of size, shape, growth habit, bark, leaves, flowers, fruit, flowering and fruiting times, habitat, and range maps for native species, as well as specially commissioned artwork, up-to-date taxonomy and names, information on the most recently naturalized species, keys to leaves and twigs, and an introduction to tree identification, forest ecology, and plant classification and structure.